Mental toughness profile as one of psychological predictors of injuries among Malaysian professional football players - Mohd Nor, Mohad Anizu; N., Kumaraswamy; R., Singh; M., Rusli (2003)
Injury is one of the common occurrence one can observe in most of the sports and games, which can occur either by accident or intentionally. There are many reasons for the factors occurrence of injuries and that psychological aspect can be considered as one of the factors. Therefore, the objective of the study is to determine whether mental toughness can be used as psychological predictors of athletic injuries in Malaysian football players involved in the 2001 Malaysian Professional Football League. A descriptive method of research was used to determine the psychological predictors of injury among the selected state team players. A pilot study was carried out to test the validity and reliability of the questionnaire. Cluster sampling was used to get the actual number of subjects. Based on this sampling method, all teams were clustered into five groups (North, South, East, West and East Malaysia). From these five groups, two teams from each cluster were randomly picked. All players in each team were recruited (25 players each team x 10 teams = 250 players). Questionnaires, observation, and interview were the instruments used in determining psychological predictors of injuries. Chi-square test was used to know the association between injured and non-injured players and injuries. Then, univariate and Multivariate Logistic Regression was also used to identify the psychological predictors of injuries by using the Statistical Package for Social Science (SPSS) version 11.0 for windows. This study indicated that majority of the Malaysian professional football players involved in Malaysia Football League have problems with mental toughness. Most of them have poor emotional stability with poor impulse control. Analysis also showed that these players had the highest incidence of injuries. In conclusion, the results indicated that mental toughness can be used as one of the psychological predictor of injuries in Malaysian Professional Football Players. It is recommended that these players attend awareness programme and also educate them with stress and mental toughness.